MENGUAK METAFORA DALAM PEMBELAJARAN SASTRA - Widjajanti, Anita (Jurnal Pengembangan Pendidikan, 2006)
Abstract. Studying literature is nationalmandatory. It is often in hibited by disability of  student in appreciating literature,especially related to figure of speech (metaphora), because of that thing wehope the teacher is able to guide the student to find out a varions contexts.That is what forms the back ground of literary works, is that a linguistic context,physical context, social context, and epistemology context. Key word            : Studyingliterature, metaphore and contxts.